Morality Politics in Western Europe - Engeli, Isabelle. author. aut Link
XI, 216 p.
Keywords: Why do some countries have 'Culture Wars' over morality issues such as abortion and same-sex marriage while other countries hardly experience any conflict? This book argues that morality issues only generate major conflicts in political systems with a significant conflict between religious and secular parties.